Concept Of Reward And Punishment And Its Implementation In Education In The Modern Era: Perspectives From The Quran And Hadith - Soleyadi, Muhammad Rois (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
Reward, as a positive stimulus, aims to strengthen desired behavior, while punishment, as a negative response, is directed at reducing undesirable behavior. These concepts reflect the ideas of reward and sin in Islam, with the Quran and Hadith providing guidance. The Quran employs terms such as tsawab and ‘iqaab to depict reward and sin. For example, in Surah Ali Imran verse 148, Allah emphasizes the provision of recompense in the world and good rewards in the Hereafter. In the educational context, rewards are not only material but also non-material, such as praise and recognition. Hadith also offers guidance on the concept of punishment in education. For instance, it indicates that educating a child involves specific stages, with physical punishment as an option when a child reaches the age of ten. Despite the allowance for punishment, affection, and gradual learning remain prioritized. In the context of implementing the concepts of reward and punishment in the modern era, the article notes new challenges in education and changes in perspectives on physical punishment. The article also discusses forms of rewards, such as verbal and non-verbal praise, symbols, enjoyable activities, and respect. Punishment is categorized into three types: associative, logical, and normative, with considerations for balance, context, consistency, psychological awareness, and alternative learning. By referencing Islamic teachings and modern psychological concepts, this article illustrates the importance of implementing reward and punishment wisely in the educational context to achieve character formation goals without compromising the psychological well-being of individuals.   Keywords: Education, Punishment, Reward, Modern Era